2017
DOI: 10.1016/j.brainres.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of proBDNF and BDNF in dendritic spine plasticity and depressive-like behaviors induced by an animal model of depression

Abstract: Major depressive disorder (MDD) is one of the most common psychiatric disorder, but the underlying mechanisms are largely unknown. Increasing evidence shows that brain-derived neurotrophic factor (BDNF) plays an important role in the structural plasticity induced by depression. Considering the opposite effects of BDNF and its precursor proBDNF on neural plasticity, we hypothesized that the balance of BDNF and proBDNF plays a critical role in chronic unpredicted mild stress (CUMS)-induced depressive-like behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 62 publications
(79 reference statements)
4
49
0
1
Order By: Relevance
“…Interestingly, the precursor protein proBDNF was strongly increased upon infection. Particularly, signaling of proBDNF via the p75 NTR has been shown to promote spine pruning and to negatively affect dendritic spine density and synaptic plasticity (Orefice, Shih, Xu, Waterhouse, & Xu, ; Qiao, An, Xu, & Ma, ; Yang et al, ). In addition, our data imply that activated immune cells contribute to proBDNF production upon infection‐induced inflammation since previous studies also observed the secretion of proBDNF by peripheral macrophages under certain inflammatory conditions (Luo et al, ; Wong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the precursor protein proBDNF was strongly increased upon infection. Particularly, signaling of proBDNF via the p75 NTR has been shown to promote spine pruning and to negatively affect dendritic spine density and synaptic plasticity (Orefice, Shih, Xu, Waterhouse, & Xu, ; Qiao, An, Xu, & Ma, ; Yang et al, ). In addition, our data imply that activated immune cells contribute to proBDNF production upon infection‐induced inflammation since previous studies also observed the secretion of proBDNF by peripheral macrophages under certain inflammatory conditions (Luo et al, ; Wong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the blockade of α7nAChR significantly increased the neurotrophin levels in hippocampus. Once the method used detects total BDNF, this effect could be related to an increase in proBDNF that is known to reduce spine density and NMDA receptor and postsynaptic density protein 95 (Qiao, An, Xu, & Ma, ). So, this observation deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated an association between marked deficits in synaptic proteins and dysregulation of mTOR signaling in depressed subjects. Furthermore, activation of mTOR is associated with local protein synthesis in the synapse, promoting the expression of proteins for synaptic connections such as PSD95 (Qiao, An, Xu, & Ma, ). Of note, the behavioral data that indicate that antidepressant‐like effect of the SCF and SD (12 hr) is dependent on activation of mTOR was reinforced by western blot results.…”
Section: Discussionmentioning
confidence: 99%